A Case of Quadruple Trouble: SLE's Multi-System Onslaught - Morgom, Marwa; Alhaj, Mona M.; Awadelseed, Sujood Musa; Alasfari, Mohamed Taher (Brazilian Journal of Case Reports, 2024)
This case report presents a diagnostic challenge in a 27-year-old Sudanese female with no past medical history who presented to the emergency department with progressive shortness of breath and pleuritic chest pain. Investigations revealed a constellation of findings suggestive of systemic lupus erythematosus (SLE) with serositis, pleuritic chest pain, pericardial effusion, pleural effusion, and positive autoimmune markers. However, the case became further complicated by the development of acute kidney injury (AKI) and the discovery of a fixed inferior vena cava (IVC) thrombosis during her hospitalization. This report highlights the complexities of SLE presentation, particularly the potential for coexisting diagnoses and the importance of a comprehensive diagnostic approach.